THE EQUALITY MEANING OF SWEARING WORD IN DAILY CONVERSATION - Kusumastuti, Risnandari; Supriadi, Putri Angelina (IKIP Siliwangi, 2018)
This article aims to investigate equality meaning or synonym of swearing words in two language are English and Sundanese, other than this research was known the participants about meaning of swearing words in daily conversation. 44 people in one college with random sample technique answered the eleventh question in questioner with their perception of swearing words, and the transcript of daily conversation used to analyze their frequency and understanding about it. The results showed that 80% of participants did not understand with synonym of two language used, but almost in their daily conversation used it. Results can be inferred that people who use the swearing words did not certainly with meaning of it, they only say everything of swearing words but did not known about the meaning.